THE ANALYSIS OF PROSPECTS OF USING COAL AT THE OBJECTS OF SMALL DISTRIBUTED GENERATION - O. V. Afanaseva; A. A. Galkeeva; A. R. Vafin; G. R. Mingaleeva (Известия высших учебных заведений: Проблемы энергетики)
In the article the prospects of using local solid fuel as an energy resource at the objects of small distributed generation is analyzed. The estimation of coal supply of Russian regions is carried out. Coal reserves for each of the regions are reduced to the unitary parameters - per head of the population, area and gross regional product which allowed a comparative assessment with the identification of regions where the location of low-capacity power plant is preferable.